1997
DOI: 10.1021/js970023k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Penetration Enhancers and Iontophoresis on the Ultrastructure and Cholecystokinin-8 Permeability through Porcine Skin

Abstract: The present study explores the effect of chemical penetration enhancers and iontophoresis on the in vitro permeability of cholecystokinin-8 (CCK-8) through porcine epidermis and on the ultrastructural changes in stratum corneum as observed by transmission electron microscopy (TEM). Enhancer [i.e., ethanol (EtOH), and 10% oleic acid in combination with ethanol (OA/EtOH)] pretreatment significantly increased (p < 0.01) the permeability coefficient of CCK-8 in comparison with the control (pretreated epidermis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Our study demonstrates that all the formulations shifted the spectral bands to higher wavenumbers which result in a blue shift of CH stretching. This may be due to the increase in the degree of disorder of the lipid acyl chains, resulting in the increased fluidity of SC (33).…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates that all the formulations shifted the spectral bands to higher wavenumbers which result in a blue shift of CH stretching. This may be due to the increase in the degree of disorder of the lipid acyl chains, resulting in the increased fluidity of SC (33).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the enhanced transdermal absorption of SA iontophoretically by the presence of ethanol in a drug solution is not due to the increased current density in vivo, but probably due to the direct action of ethanol on the stratum corneum. It is reported that pretreatment of skin surface with absolute ethanol caused a loss of structural components in the superficial stratum corneum cell layers [8]. Also, burns are sometimes caused by iontophoresis [14].…”
Section: Resultsmentioning
confidence: 99%
“…The pretreatment effect of ethanol on the skin surface has been reported by several investigators, in which the ethanol pretreatment prior to iontophoresis dramatically increased the transdermal absorption of insulin, leutinizing hormone releasing hormone and cholecystokinin-8 [6][7][8]. Regarding the direct effect of ethanol in a drug solution in iontophoresis, however, there is no report available, except our previous reports [9,10].…”
Section: Introductionmentioning
confidence: 88%
“…Because high-molecular-weight drugs cannot be delivered using a single method, some combination systems -iontophoresis as a physical method plus chemical penetration enhancer as a chemical method -have been suggested to solve this problem [4][5][6][7]. However, the mechanism of their synergistic effect has not been reported from in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…A problem with the iontophoretic drug delivery system is how to overcome the resistance of the SC, the main permeability barrier, for more effective penetration with less side effects. Some researches in in vitro skin studies have shown that pretreatment with a chemical penetration enhancer before iontophoresis increases the penetration of high-molecular-weight drugs [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%